Developing multilingual education policies theory, research, practice - Tannenbaum, Michal; Shohamy, Elana Goldberg (Routledge, Taylor & Francis Group, 2023)
"Multilingual policies are increasingly important and required in educational settings worldwide, yet there lacks a solid experimental body of theory, research and practice, providing guidance for the development of policies. The Israeli context presented in this book serves as a case study or a model that could be used by bodies or entities seeking to devise a multilingual policy. Divided into three parts, the authors begin by addressing the general notion of a multilingual education policy with specific reference to the Israeli context. The book then focuses on specific challenges confronting the new policy that have been explored in empirical studies and concludes with a proposed framework for a new multilingual education policy related to the core theoretical topics and empirical findings discussed in the previous chapters. This framework includes principles and strategies for implementing the process described in the book in other contexts, ensuring wide applicability and relevance. Developing Multilingual Education Policies: Theory, Research, Practice is an essential read for all involved in language policy and planning within Applied linguistics and education"--